MENINGKATKAN LOYALITAS DENGAN KUALITAS PELAYANAN DAN PROMOSI MELALUI KEPUASAN TAMU DI HOTEL JS LUWANSA - Tarizka Luthfiyah; Rivera Silitonga (Human Capital Development, 2022)
The purpose of this study was to determine the effect of service quality and promotion on loyalty through guest satisfaction at Hotel JS Luwansa. This study uses a quantitative method that is processed with SPSS version 23 and path analysis method. With a total of 190 respondents and using purposive sampling technique. The results of this study indicate that service quality has a significant effect on guest satisfaction and guest loyalty. Promotion has a significant effect on guest satisfaction and has no effect on guest loyalty. Guest satisfaction has a significant effect on guest loyalty. Service quality and promotion have an indirect and significant effect on guest loyalty through guest satisfaction. Keywords: Service quality, promotion, satisfaction, loyalty